Improving grid reliability through application of protection security assessment - Bopp, T. A.; Ganjavi, R.; Krebs, R.; Ntsin, B.; Dauer, Maximilian; Jäger, Johann (IET Conference Publications, 2014)
Key findings derived by the application of an automated protection security assessment solution on a nationwide transmission system are presented. Protection coordination and verification of settings through simulation is getting increasingly complex. Conventional protection coordination and simulation tools reach their limits of practical applicability for fast developing networks and changing operating conditions. New automated protection security assessment solutions can overcome existing limitations and allow the fast and systematic performance assessment of the protection system. A new approach to assess the adequacy of protection settings and schemes is presented. It facilitates the verification of selectivity of protection settings for large numbers of different operation and fault scenarios. The presented solution is capable to handle large and complex network structures, and also to analyze the system behavior of the protection system and network as a whole. New concise result visualizations were developed to support protection engineers and operators to identify potential weak points and limitations of the protection schemes and settings. The paper summarizes key findings and lessons learnt from an automated systematic protection performance assessment and enhancement project performed on a nationwide transmission system. It demonstrates how the applied solution can help to assure and improve the quality of protection settings through event-triggered or regular application. The in-depth evaluation allows the pinpointing of false settings in individual relays and for various different operating and fault conditions. If false or improvable settings are detected then the solution supports the calculation of new improved protection settings. To enhance quality control, a new set of settings can be validated and verified through simulation before application in order to maximize network utilization and grid reliability by reducing the risk of unwanted protection actions and cascading events.
Created from Fastlane, Scopus look-up
Keywords: Automated protection performance assessment